A frequency-domain procedure to design TMDs for lively pedestrian structures considering Human–Structure Interaction. (September 2022) - Gallegos-Calderón, Christian; Renedo, Carlos M.C.; Pulido, M. Dolores G.; Díaz, Iván M.
Abstract: The use of advanced low-density high-strength materials, such as Fibre Reinforced Polymers (FRPs) or aluminium alloys, has enabled to construct lightweight and slender footbridges, which structural design may be governed by the Vibration Serviceability Limit State (VSLS) under human-induced loads. These structures may be excited in resonance by higher and less energetic harmonics of human actions in contrast to footbridges built with traditional construction materials. Additionally, Human–Structure Interaction (HSI) may be relevant on the dynamic response of these type of pedestrian structures. A solution for the aforementioned issues may be the installation of Tuned Mass Dampers (TMDs) in the bridge. Thus, this paper presents a frequency-domain procedure to design TMDs for lively pedestrian structures based on a coupled Human–Structure–controller system. The proposal, which accounts for uncertainties associated to the structure and the interaction phenomenon, is applied to design passive inertial control systems for an FRP footbridge. Also, the implications of HSI in the design of TMDs are discussed, and the performance of the designed devices is assessed considering two human actions, bouncing and walking. Since the peak value of the steady-state response of a pedestrian structure can be fast assessed through algebraic operations, the proposed approach is suitable to design robustly control systems against human-induced vibrations. As a result, structural elements and controllers can be properly dimensioned, leading to further cost-effective footbridge projects.